Meta Analysis of Factors Associated with Job Satisfaction in Health Workers - Hapsari, Fara Rizky Punjung; Murti, Bhisma; Tamtomo, Didik (Journal of Health Policy and Management, 2023)
Background: Job satisfaction is a perception that is reflected in attitude and focused on behavior towards a job, and is a form of human interaction with the work environment.  High job satisfaction is a sign that an agency has done good management. The more satisfied the health workers in an institution, the more maximum their level of performance and productivity so that the goals of the institution can be achieved. The study aims to analyze the factors that affect job satisfaction in health workers based on the results of previous similar studies. Subjects and Method: It was a systematic review and meta-analysis study with the PICO as follows: P = health workers, I = high salary, the availability of supervision C = low salary, no supervision O = job satisfaction. The data collection was conducted through the databases, namely: Google Scholar and PubMed. The inclusion criteria used were full English papers with Cross Sectional designs in 2012-2022. The keywords used were “job satisfaction" AND "Associated factors” AND "Health Worker".  The articles were analyzed using the Review Manager 5.3 application. Results: The meta-analysis was conducted on 8 primary studies from several countries such as Ethiopia, China, and Nepal. The results of the study showed that there was an effect of high salary on job satisfaction.  Based on the analysis, high-paid health workers were 1.88 times more likely to be satisfied than low-paid health workers and it was statistically significant (aOR = 1.88; CI 95% = 1.08 to 3.2; p = 0.020). Furthermore, a meta-analysis was conducted on 7 primary studies from northern and eastern parts of Ethiopia. The results of the study showed that there was an effect of supervision on job satisfaction. Healthcare workers who received supervision were 2.93 times more likely to be satisfied than those who were unsupervised and it was statistically significant (aOR = 2.93; CI 95% = 1.51 to 5.66; p= 0.003). Conclusion: The provision of high salaries and supervision increases the job satisfaction of health workers.   Keywords: job satisfaction, related factors, health workers. Correspondence: Fara Rizky Punjung Hapsari. Masters Program in Public Health, Universitas Sebelas Maret. Jl Ir Sutami no 36 A, Surakarta, Central Java 57126, Indonesia. Email: fararizky92@gmail.com. Mobile Phone: 081230388935.